Interlaminar shear strength of vacuum pressure impregnated coils with epoxy resin for high field magnet at cryogenic temperature. Issue 1 (1st May 2022) - Wang, Chundong; Zhao, Yalin; Liu, Huiming; Fang, Zhichun; Xin, Jijun; Wu, Zhixiong; Huang, Chuanjun; Huang, Rongjin; Li, Laifeng
Abstract: The interlaminar shear properties of epoxy impregnated coils are critical parameter to the design of the high field superconducting magnets. The existing test methods of the interlaminar shear strength of the composite insulation systems for the superconducting magnet coils in cryogenic temperature were discussed. The insulation system of the niobium titanium superconductor coated with woven glass fiber reinforced polymer coil were fabricated by vacuum pressure impregnation with IR-3 and CTD-101K resins. Short beam shear tests of the impregnated coil were performed at room temperature and liquid nitrogen temperature (77K). The results show that the interlaminar shear strength of the samples used IR-3 resin are better than CTD-101K both at room and cryogenic temperature. A detailed observation of the failed specimens was also investigated to verify the failure mechanisms by optical microscopy.